INDIKATOR OUTPUT KELAS IBU HAMIL DI PUSKESMAS PONED KABUPATEN BANJARNEGARA TAHUN 2016 - Sulistyorini, Dewie (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
The efforts at decreasing MMR should be done by integrating several related programs from the beginning of pregnancy, childbirth, childbed, infant, toddler and couples of childbearing age. The occurrence of maternal and neonatal death depends on the speed and accuracy of the action when the emergency occurs. The presence of Public Health Center capable of PONED is one of the answers to close community access toward to midwife and newborn care to prevent complication and or get first service when emergency obstetric and newborn emergency condition with service requirement fulfill adequate service standard. Maternal Woman class is group studying pregnant mothers with gestational age between 20 weeks to 32 weeks (before childbirth) with maximum number of participants 10 people. In this class, pregnant women will learn together, discuss and exchange experiences about mother and child health as a whole and systematically and can be carried out on a scheduled and continuous basis. The purpose of this research is to know the monitoring and evaluation the implementation of pregnant class at PONED Public Health Center at working area of ​​Banjarnegara Regency. The purpose of this research is to know the monitoring and evaluation of pregnant class implementation in PONED Public Health Center at work area of ​​Banjarnegara Regency. The indicator of maternal class success consists of 3 things: input indicators, process indicators and out put indicators. The result of the research is 1). All (100%) Pregnant women have Maternal Children Health books. 2). Most of them (92%) K4 100% which means it has met the target. Only 1 Public Health Center (8%) alone have not met the target because only (79.7%). 3). All (100%) Pregnant women who fill P4K. 4). Most (92%) all (100%) pregnant women are pregnant women who get Fe tablets. Only 1 Public Health Center (8%) are not all (84.1%) pregnant women in pregnant women who get Fe tablets. 5). Most (85%) of all (100%) pregnant women are pregnant mothers who choose delivery help to health personnel either at Public Health Center, maternity clinic or hospital. There are still 2 Public Health Center (15%) which not all (98,9% and 97,2%) pregnant mother of pregnant class participant who choose delivery aid to health worker either at Public Health Center, birthing clinic or hospital. 6). Most (92%) of all (100%) pregnant women of pregnant class participants carry out the KN completely. Only 1 Public Health Center (8%) are not all (98,7%) pregnant mother of pregnant class participant carry out KN completely. 7). There are (77%) of all (100%) of babies born to pregnant women in pregnant mothers class by IMD. There are still 3 puskesmas (23%) which are not all (98,7%, 85% and 53,78%) of babies born by pregnant mother pregnant class participant is done IMD. 8). There are (61%) Public Health Center involving less than 10 cadres in the class of pregnant women and there are (39%) Public Health Center involving less than 10 cadres in the class of pregnant women.Keywords: Indicator Out put class of pregnant women